Fundamentals of Forensic Expertology as a Foundation for Training of State Forensic Experts for Forensic Institutions under the Russian Ministry of Justice in Expert Specialties - N. V. Mikhaleva (Теория и практика судебной экспертизы, 2024)
According to the Russian legislation an expert of a state forensic institution must get an additional professional education in a specific expert specialty. One of the important disciplines studied by a future expert is the Theory of Forensic Expertise, which now has transformed into Forensic Expertology. The article analyses a textbook “Fundamentals of Forensic Expertology” prepared in the Russian Federal Centre of Forensic Science under the Ministry of Justice of Russia for students who receive additional professional training in expert specialties, which is basic for the corresponding course of lectures. The author outlines some practical steps necessary for the transition to training the future experts in the basics of forensic expertology.